Managing Persistent Tensions on the Frontline: A Configurational Perspective on Ambidexterity - Zimmermann, Alexander; Raisch, Sebastian; Cardinal, Laura B. (Journal of management studies, 2018)
Ambidexterity research has noted that firms’ simultaneous pursuit of exploration and exploitation causes organizational tensions that are difficult to resolve. To make these tensions manageable, scholars have generally suggested that senior managers take the central role in designing organizational solutions, such as the structural separation or contextual integration of the exploratory and exploitative tasks. Yet, in an inductive study of ten corporate innovation initiatives, we find that our informants assigned far less importance to the senior managers’ initial design choices than to the frontline managers’ subsequent configurational practices. Frontline managers used these practices to constantly adapt and align their initiatives’ organizational contexts, which allowed them to cope with persistent exploration‐exploitation tensions in their daily business activities. Based on these empirical insights and drawing on paradox theory, we develop a configurational perspective on ambidexterity, where frontline managers play a more central, proactive, and strategic role than purported by the established design perspective on ambidexterity.